2020
DOI: 10.1002/ajmg.a.61606
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking as an objective measure of hyperphagia in children with Prader‐Willi syndrome

Abstract: This study examined sensitivity of eye tracking measures to hyperphagia severity in Prader-Willi syndrome (PWS). Gaze data were collected in 57 children with PWS, age 3-11 years, and 47 typically developing peers at two study sites during free visual exploration of complex stimulus arrays that included images of food, animals, and household objects. Analysis of the number and duration of fixations as well as gaze perseverations revealed that food items are not exceptionally salient for children with PWS. Inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Two recent reports of clinical trials for hyperphagia have reported baseline mean HQ-CT scores between 15 and 18.3 in obese adolescents and adults with PWS [41,42], scores that are much higher than the mean score (12.2) we found in obese individuals in our study. Another recent clinical study also reported higher baseline mean HQ-CT scores (around 18) in children with PWS aged 3-11 y [43]. The difference of research settings may explain the higher baseline scores in these clinical studies compared to the current study.…”
Section: Plos Onecontrasting
confidence: 41%
“…Two recent reports of clinical trials for hyperphagia have reported baseline mean HQ-CT scores between 15 and 18.3 in obese adolescents and adults with PWS [41,42], scores that are much higher than the mean score (12.2) we found in obese individuals in our study. Another recent clinical study also reported higher baseline mean HQ-CT scores (around 18) in children with PWS aged 3-11 y [43]. The difference of research settings may explain the higher baseline scores in these clinical studies compared to the current study.…”
Section: Plos Onecontrasting
confidence: 41%
“…This observer-reported outcome measure, which aims to measure more objective food-related behavior, is based on behaviors over the past 2 weeks reported by a caregiver who is familiar with the daily activities of the person with PWS. Beyond self- or observer-reported assessment of hyperphagia in PWS, there is interest in the field for developing assessment tools that employ objective, direct measures of food interest, such as eye gaze or evoked response potentials [ 46 , 47 ].…”
Section: Hyperphagia In Pwsmentioning
confidence: 99%
“…However, findings concerning the association between genetic subtypes in PWS and food-related problems are inconclusive. For instance, higher food-related problems were found in individuals with microdeletion than those with mUPD ( 19 ) while Key et al ( 26 ) found a longer fixation on food stimuli using an eye tracking experimental procedure (a proxy measure of problematic food interest), in mUPD subtype than the deletion subgroup.…”
Section: Introductionmentioning
confidence: 99%